The impact of small-scale irrigation on household food security: the case of Filtino and Godino irrigation schemes in Ethiopia - Tesfaye, A.; Bogale, A.; Namara, Regassa E.; Bacha, D. (2008)
Ethiopia's irrigation potential is estimated at 3.7 million hectare, of which only about 190,000 ha (4.3% of the potential) is actually irrigated. There is little information on the extent to which the so far developed irrigation schemes have been effective in meeting their stated objectives of attaining food self-sufficiency and eradicating poverty. Therefore, the aim of this paper is to identify the impact of small-scale irrigation on household food security based on data obtained from 200 farmers in Ada Liben district of Ethiopia in 2006. The resulting data was analyzed using Heckman's Two-step Estimation procedure. Studies elsewhere revealed that access to reliable irrigation water can enable farmers to adopt new technologies and intensify cultivation, leading to increased productivity, overall higher production, and greater returns from farming. Our study findings confirm some of these claims. In the study area about 70% of the irrigation users are food secure while only 20% of the non-users are found to be food secure. Access to small scale irrigation enabled the sample households to grow crops more than once a year; to insure increased and stable production, income and consumption; and improve their food security status. The study concludes that small- scale irrigation significantly contributed to household food security.